Status Mental Lansia di PSLU Tulungagung - Nopia Riana Dewi (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2014)
Old age is the final stage of the human life cycle and will inevitably be experienced by every individual, who will undergo physical and mental changes. The purpose of this study was to describe the mental status of the elderly. Method: Research design was descriptive study. The population in this study is 80 elders who live in PSLU Tulungagung in March 2014, Sample were 45 elderly by using purposive sampling technique. The data collected by  using a questionnaire MMSE at May 18th until 19th, 2014. Results: The result showed that 53.3% no cognitive impairment, 20% and cognitive impairment was 26.7% experiencing severe cognitive impairment. Discussion: It is expected that the results of this study, health workers improve activities that are motivating and supporting the elderly in dealing with elderly dementia or memory to support the mental status of the elders.